The cytoplasmic domain of neuropilin‐1 regulates focal adhesion turnover. Issue 21 (8th September 2013) - Seerapu, Himabindu Reddy; Borthakur, Susmita; Kong, Nathan; Agrawal, Sudesh; Drazba, Judy; Vasanji, Amit; Fantin, Alessandro; Ruhrberg, Christiana; Buck, Matthias; Horowitz, Arie
Abstract : Though the vascular endothelial growth factor coreceptor neuropilin‐1 (Nrp1) plays a critical role in vascular development, its precise function is not fully understood. We identified a group of novel binding partners of the cytoplasmic domain of Nrp1 that includes the focal adhesion regulator, Filamin A (FlnA). Endothelial cells (ECs) expressing a Nrp1 mutant devoid of the cytoplasmic domain ( nrp1 cyto Δ/Δ ) migrated significantly slower in response to VEGF relative to the cells expressing wild‐type Nrp1 (nrp1 +/+ cells). The rate of FA turnover in VEGF‐treated nrp1 cyto Δ/Δ ECs was an order of magnitude lower in comparison to nrp1 +/+ ECs, thus accounting for the slower migration rate of the nrp1 cyto Δ/Δ ECs. Abstract : Neuropilin‐1 (Nrp1) bound filamin A (FlnA) directly. Endothelial cells (ECs) expressing Nrp1 lacking a cytoplasmic domain migrated slower than wild type ECs. Focal adhesion (FA) turnover in ECs expressing truncated Nrp1 was slower than in wild type ECs.